Cyclic tests of post-tensioned precast CFT segmental bridge columns with unbonded strands. - Chou, Chung-Che (Earthquake engineering & structural dynamics.)
Two ungrouted post-tensioned, precast concrete-filled tube (CFT) segmental bridge columns were tested under lateral cyclic loading to evaluate the seismic performance of the column details. The specimens included a load stub, four equal-height circular CFT segments, and a footing. Strands were placed through the column and post-tensioned to provide a precompression of the column against the footing. One specimen also contained energy-dissipating devices at the base to increase the hysteretic energy. The test results showed that (1) both specimens could develop the maximum flexural strength at the design drift and achieve 6% drift with small strength degradation and residual displacement, (2) the proposed energy-dissipating device could increase energy dissipation in the hysteresis loops, and (3) the CFT segmental columns rotated not only about the base but also about the interface above the bottom segment. This study proposed and verified a method to estimate the experimental flexural displacement using two plastic hinges in the segmental column.